Comment on “Reversing cultural identity in the West: the 1935-1936 International Exhibition of Chinese Art in London: in philosophical perspective” - Yaomin Huang (Trans/Form/Ação)
Commented article: LIU, Y. H. Reversing cultural identity in the West: the 1935-1936 International Exhibition of Chinese Art in London: in philosophical perspective. Trans/Form/Ação: Unesp journal o philosophy, Marília, SP, v. 48, n. 5, p. e025047, 2025. Available at: https://revistas.marilia.unesp.br/index.php/transformacao/article/view/16972.